Pengaruh Permainan Lego terhadap Kemampuan Kreativitas Anak Usia Dini di TK IT Bunayya 7 - DN, Widia Ulan Dary; Nurmawati, Nurmawati; Nasution, Inom (Asian Journal of Early Childhood and Elementary Education, 2024)
The research that was conducted was entitled "The Influence of Lego Games on the Creativity Abilities of Early Childhood in Kindergarten IT Bunayya 7", researchers saw that some children's creative abilities had not yet developed, only a few children's creativity had begun to develop. The research methodology used is a quantitative methodology with a pre-experimental design one group pretest posttest approach. The research population was children from the Al-Quddus class at TK IT Bunayya 7 with a sample size of 15 children. Data collection techniques using observation, tests, documentation. Researchers use the SPPS application to facilitate data processing, namely validity testing, reliability testing, normality testing and hypothesis testing. The results of the research reveal that (1) Lego games have an effect on the creative abilities of young children in Kindergarten IT BUNAYYA 7 (2) obtained from the results of the t test analysis (paired sample t-test), it can be obtained that tcount > ttable (ǀ-5.113 ǀ (absolute) > 2.145) and Sig. (2 tailed) = 0.000 < 0.05, which means there is a significant influence on children's creativity between before and after using Lego learning media. (3) The effect size of the Lego game is that a Cohen's d value is 1.3. And in the interpretation table, the value of Cohen's d is 90% which can be categorized as large.